2014
DOI: 10.20344/amp.4229
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Reason for a Medical Visit in Lung Cancer Patients

Abstract: Background:Patients with lung cancer usually present with symptoms at the time of diagnosis, but it is common that neither the doctor nor the patient initially associate them with the possibility of a malignant tumour. Objectives: The aim of our study is to analyse the symptoms of patients with lung cancer and the relationship with the personal characteristics or the oncological disease. Material and Methods:A retrospective study was conducted on all patients diagnosed with lung cancer in the Pontevedra Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Hence, in the meantime, much attention has also been paid to symptoms, especially initial respiratory symptoms, that may indicate the incidence of lung cancer 10 - 12 . It was suggested that many patients with lung cancer had subtle shifts in symptoms when they were diagnosed and the majority of them were actually caused by the cancer 13 , 14 . Several studies have consistently demonstrated that presence of hemoptysis is well associated with lung cancer diagnosis and acts as the strongest symptom predictor of lung cancer in those high-risk population 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the meantime, much attention has also been paid to symptoms, especially initial respiratory symptoms, that may indicate the incidence of lung cancer 10 - 12 . It was suggested that many patients with lung cancer had subtle shifts in symptoms when they were diagnosed and the majority of them were actually caused by the cancer 13 , 14 . Several studies have consistently demonstrated that presence of hemoptysis is well associated with lung cancer diagnosis and acts as the strongest symptom predictor of lung cancer in those high-risk population 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%